การประกันภัยความรับผิดของผู้ประกอบการขนส่งต่อเนื่องหลายรูปแบบ : ศึกษาเฉพาะกรมธรรม์ประกันภัยความรับผิดที่ใช้ในสมาคมผู้รับจัดการขนส่งสินค้าระหว่างประเทศแห่งประเทศไทย - สวรส สุวรรณวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The term "multimodal transport" means the carriage of goods by at least two different modes of transport where the multimodal transport operator (MTO) is the only one who directly makes an agreement with the consignor and undertakes to be responsible for losses or damages arising from any engagement pursuant to the agreement. Since Multimodal Transport Act 2005 has entered into force, it is compulsory that the MTO has a guarantee for the liability in accordance with multimodal transport agreement as well as any risk pertaining to the agreement. In addition, such guarantee needs to be maintained as long as he remains in multimodal transport business in Thailand. In order to set a management quality standard and increase the potentials of its members, Thailand International Freight Forwarders Association: TIFFA made attempts to provide the guarantee required by the Act of Parliament. TIFFA, in cooperation with Chubb Insurance (Thailand) Co.,Ltd., considered the revision of the liability insurance policies available in the market before the entry into force of the Act, most of which had mainly focused on marketing value for the operators – only transferring the obligation to indemnify those suffered from loss or damage to the insurer without taking into account of fair compensation. The improved liability insurance policies correspond with the criteria set out by the Act and make the system of indemnity efficient. Two forms of policy to insure the liability of multimodal transport operator were drafted and they provide an opportunity for MTO to choose the form suitable for its own operations. Those policies have been approved by the registrar under the laws of General Insurance and available for offering coverage in multimodal transport system. As per research, it is found that although two forms of liability insurance policy initiated TIFFA manage to specify the provisions of indemnity conformable to the criteria of multimodal transport operator s liability in accordance with the Multimodal Transport Act and can give assurance to the consignor or consignee that he can obtain the indemnity in case of losses and damages, the amount of insurance should be fixed in a way that will sufficiently cover the limit of the liability of MTO according to the Act so that the objective to effectively remedy the consignor or consignee will fully be met.